Implementation of Land Value Zoning Utilization Policy in Calculation of the Value of Non-Tax State Revenue and Regional Development Planning of Medan - Tanjung, Ahmad Riadi; Erlina, Erlina; Sirojuzilam, Sirojuzilam (Budapest International Research and Critics University, 2021)
The research found that the communication dimension of implementation has not yet been fully implemented. Communication is done conventionally through the use of formal channels while unconventional, especially during the pandemic, is done through information technology. Monitoring and evaluation methods and problem solving are one of the weak points of implementation, such as the lack of participatory involvement in policy implementation. The dimensions of resources both related to capital resources and social resources are very adequate, but human resources related to the quantity and quality of policy implementers are still far from ideal. This study also finds that the bureaucratic structure of policy implementation which is only led by echelon III officials is not yet feasible to carry out land services optimally. However, standard operating procedures (SOP) in the service have been present even though they have not been simplified through documents such as service SOPs and SPM. The disposition dimension has been well institutionalized, such as regulations regarding code of ethics standards, reporting mechanisms for corrupt acts and internal controls. This study concludes that the use of ZNT in determining PNBP and also regional development has not been carried out optimally. This happens because the technical instruments used in land electronic services have not been well planned. This study further recommends the need to prioritize participatory mechanisms in policy implementation, recruitment of ASN along with the required competency standards, increasing the status or typology of the land office and creating a special platform for reporting on corrupt practices, collusion and abuse of authority by policy implementers.